Delmar's agroscience dictionary with searchable CD-ROM - Herren, Ray V. (Delmar Publishing, 2000)
Provides definitions for more than 15000 terms in the fields of Animal Science, Business and Mechanical Technology, Forestry and Natural Resources Management.